Building energy analysis using cooling load factor/cooling load temperature different (CLF/CLTD) - Mohd Firdaus, Musa (2010)
This project is carried out to indentify whether the existing cooling capacity is suffice for an occupied building. The first objective of this project is to determine the heat gain of FKM Administration Building when it’s fully occupied. The second objective of this project is to compare the calculated heat gain against the existing cooling capacity. FKM Administration Building was chosen as the case study. The architectural drawing of FKM Administration Building is first studied to review the building specifications. The building specification is used in the calculation of heat gain in order to identify the cooling load required for FKM Administration Building. When FKM Administration Building is fully occupied, the number of occupant will be around 396 peoples. The type of air-conditioning system used in FKM Administration Building is central air conditioning system and the total existing cooling load is observed to be 381.8 kW. The peak heat gain is calculated as 492.7 kW using Cooling Load Factor/ Cooling Load Temperature Difference (CLF/CLTD) method at 4 pm. Therefore, the existing cooling load is observed to be undersized in design. However, the peak heat gain will only happen occasionally throughout the year. In order to overcome the undersized design cooling capacity problem, the cooling capacity should increase 29%.